1989
DOI: 10.1289/ehp.8980127
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the differentiation of PC12 pheochromocytoma cells.

Abstract: The PC12 clone, developed from a pheochromocytoma tumor of the rat adrenal medulla, has become a premiere model for the study of neuronal differentiation. When treated in culture with nanomolar concentrations of nerve growth factor, PC12 cells stop dividing, elaborate processes, become electrically excitable, and will make synapses with appropriate muscle cells in culture. The changes induced by nerve growth factor lead to cells that, by any number of criteria, resemble mature sympathetic neurons. These change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
193
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(196 citation statements)
references
References 238 publications
(153 reference statements)
3
193
0
Order By: Relevance
“…Because of the clonal instability of the PC12 cell line [33], the experiments were performed on cells that had undergone fewer than five passages. As described previously [62,85], PC12 cells (American Type Culture Collection, 1721-CRL, obtained from the Duke Comprehensive Cancer Center, Durham, NC) were seeded onto poly-D-lysine-coated plates in RPMI-1640 medium (Invitrogen, Carlsbad, CA) supplemented with 10% inactivated horse serum (Sigma Chemical Co., St. Louis, MO), 5% fetal bovine serum (Sigma Chemical Co.), and 50 μg/ml penicillin streptomycin (Invitrogen).…”
Section: Cell Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the clonal instability of the PC12 cell line [33], the experiments were performed on cells that had undergone fewer than five passages. As described previously [62,85], PC12 cells (American Type Culture Collection, 1721-CRL, obtained from the Duke Comprehensive Cancer Center, Durham, NC) were seeded onto poly-D-lysine-coated plates in RPMI-1640 medium (Invitrogen, Carlsbad, CA) supplemented with 10% inactivated horse serum (Sigma Chemical Co., St. Louis, MO), 5% fetal bovine serum (Sigma Chemical Co.), and 50 μg/ml penicillin streptomycin (Invitrogen).…”
Section: Cell Culturesmentioning
confidence: 99%
“…Finally, we compared the effects of the in vivo chlorpyrifos treatment with those in PC12 cells, a standard in vitro model of mammalian neurodevelopment [89] that reproduces many of the key mechanisms and features of the adverse effects of organophosphates on neural cell replication and differentiation [6,26,42,61,72,73,85]. In response to NGF, PC12 cells exit the mitotic cycle and differentiate into cholinergic and catecholaminergic phenotypes, possessing axonal projections, electrical excitability, cholinesterase and cholinergic receptors [33,85,89]. Furthermore, the role of many of the genes examined in our study have also been confirmed in PC12 cells [86,99].…”
Section: Introductionmentioning
confidence: 99%
“…Cells were incubated with 7.5% CO 2 at 371C and the medium was changed every 2-3 days. Because of the clonal instability of the PC12 cell line (Fujita et al, 1989), the experiments were performed on cells that had undergone fewer than five passages and studies were repeated several times with different batches of cells. For evaluation of DEX effects of different durations in the undifferentiated state, cells were plated on 60 mm poly-L-lysine-coated plates at various initial densities so as to achieve approximately 70% confluence at the time of each determination, in order to avoid complete confluence and excessive clumping at the longest time points.…”
Section: Pc12 Cell Culture and Treatmentsmentioning
confidence: 99%
“…In the current study, we utilized rat pheochromocytoma PC12 cells, a model for evaluating neuronal cell replication and differentiation (Teng and Greene, 1994). In the presence of nerve growth factor (NGF), the cells gradually exit the mitotic cycle and begin to differentiate, developing axonal projections, electrical excitability, and the characteristics of two distinct phenotypes, cholinergic, and catecholaminergic neurons (Fujita et al, 1989;Song et al, 1998;Teng and Greene, 1994). These specific phenotypes are highly targeted by DEX treatment in vivo (Ebert et al, 1997;Hu et al, 1996;Kreider et al, 2005aKreider et al, , b, 2006Reznikov et al, 2004;Slotkin et al, 1991;Zahalka et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…PC12 pheochromocytoma cells have been widely used as a model for the study of neuronal differentiation (Fujita et al 1989). PC12 cells were differentiated into sympathetic-like neurons involving neurite outgrowth by treatment of NGF (Greene and Tischler 1976).…”
Section: Introductionmentioning
confidence: 99%